L’agostinismo del secolo xiv - Fiorentino, Francesco (Revue d'études augustiniennes et patristiques, 2008)
XIVth century has known a vigorous resumption of the consultation of the texts and the ideas of St. Augustin. But can it be spoken about ‘Augustinism’ in this historical age? What is Augustinism of XIVth century? The article tries to show that it is possible to affirm that the Augustinism of XIVth century has really existed. It is characterized by two principal factors: 1) the resumption of Augustin’s works; 2) the speculative tradition on Augustin’s tracks. The first factor is revealed in two different tendencies: 1) the flowering of comments to Augustin’s works, especially in English area and outside O.E.S.A.; 2) the progress of treatment of sources inside the order, which has become Augustin’s guardian since 1328. The second factor has articulated in two trends of thought: 1) Giles of Rome’s trend; 2) Gregor of Rimini’s trend. Gregor has been the founder of it on the European continent and inside the order, except Thomas Bradwardine, English Augustinian canonical. While Gregor has learned in Italy the subtilitates Anglicae, Klenkok has exported the via Gregorii to Oxford from the Order’s inside. This via is defined by four elements: 1) the most greater dependence upon Augustin; 2) the antipelagian criticism; 3) the historical-critical treatment of sources; 4) the opening to via moderna and subtilitates Anglicae. This sort of Augustinism can be considered as concluded in the beginning of the XVIth century with the printing of Augustinian corpus, which allows a direct access to the works of the Doctor Catholicus.